A3.30 Plasma level of HSP70 protein is increased in czech patients with idiopathic inflammatory myopathy. (31st January 2014) - Svitalkova, Tana; Remakova, Martina; Plestilova, Lenka; Klein, Martin; Mann, Herman; Vencovsky, Jiri; Novota, Peter
Abstract : Background and Objectives: Heat shock protein 70 (HSP70) plays an essential role as molecular chaperone by assisting the correct folding of nascent and stress-accumulated misfolded proteins, and preventing their aggregation. These proteins have a dual function depending on their intracellular or extracellular location. Intracellular HSP70 proteins have a protective, antiapoptotic role. Under normal conditions they act as molecular chaperones. Under a stress conditions, the expression of HSP70 genes is induced, which helps the cell to survive otherwise lethal condition. This is due to its important role in apoptosis. The extracellular HSP70 proteins, on the other hand, can act as mediators of immune response. They can elicit an immune response modulated either by the adaptive or innate immune system. Mechanisms of extracellular and intracellular action of Hsp70 is expected to be involved also in autoimmunity development. The aim of this study was to establish the plasma level of Hsp70 protein in patients suffering from IIM and find its possible relation to the clinical features of our patients. Materials and Methods: We quantified plasma Hsp70 levels in a healthy control group ( n = 37) and a group of 34 patient with IIM. Plasma Hsp70 protein was analysed in duplicates using a commercially available high-sensitivity sandwich enzyme-linked immunosorbent assay (ELISA), suitable for detection of Hsp70 protein in serum or plasma samples (Assay Designs EKS-715, USA). Statistical differences between the patients and control groups were established using Mann-Whitney U test. All the expression data are presented as medians with range. Results: We have found that plasma levels of Hsp70 were significantly higher in patients with myositis than in healthy controls (0.173 [0.000 – 7.647] vs. 0.000 [0.000 – 1.008] ng/ml; p<0.01). However, plasma Hsp70 levels did not correlate with age, CRP, disease activity index (MYOACT), or other clinical features (muscle activity) of our patients. Conclusions: In this study, we have found that the amount of Hsp70 protein in plasma is significantly higher in IIM patients when compared with healthy controls. Our results correlate with our former findings showing that mRNA levels of HSP70 genes were increased in myositis patients. Finally we can assume that the Hsp70 protein is possibly involved in the pathological mechanism of the myositis. Acknowledgement: This study was supported by the Internal Grant Agency of the Ministry of Health in the Czech Republic [MZČR NT 13699].